Supporting preschool children's early writing with self-regulated learning strategies - Siew, Kim Siew (Pacific Early Childhood Education Research Association, 2019)
Research suggests that early writing is crucial in the development of young children’s literacy skills and links to their conventional literacy outcomes in elementary school and beyond. In order to enhance the will and the skills to express thoughts explicitly and effectively in early writing among preschool children, self-regulated learning (SRL) was suggested. This experimental study involved seventy-five preschool children, aged from five to six years old in Malaysia, aimed to investigate the effectiveness of SRL strategies on early writing performance. In this study, quantitative data collection was engaged and supported with qualitative data through interviews to obtain a deep insight of the findings results. Two-way repeated measure ANCOVA was employed and confirmed the effectiveness SRL intervention performance in early writing. In regression analyses, strategy such as planning and goal setting was confirmed as strong predictor for early writing performance. Data from the interview revealed that various SRL strategies were engaged by out-performing children from the experimental group and contributed to their early writing performance. The findings of this research provide a useful insight into early writing instructions in Malaysian context.